2015
DOI: 10.1371/journal.pone.0141121
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Variation Has Effect on Differential Gene Expression Analysis in the Hippocampus of the Pilocarpine-Induced Model of Mesial Temporal Lobe Epilepsy

Abstract: The molecular mechanisms underlying epileptogenesis have been widely investigated by differential gene expression approach, especially RT-qPCR methodology. However, controversial findings highlight the occurrence of unpredictable sources of variance in the experimental designs. Here, we investigated if diurnal rhythms of transcript’s levels may impact on differential gene expression analysis in hippocampus of rats with experimental epilepsy. For this, we have selected six core clock genes (Per1, Per3, Bmal1, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 82 publications
2
24
0
Order By: Relevance
“…Curiously, although Ppia levels are close between 0h- and 6h-PMI ( Fig 2D ), the decreased Ppia transcript levels in acute group were significant only when compared to 6h-PMI ( Fig 3D ). Previous studies in epilepsy models indicated Ppia as a potential reference gene [ 16 , 49 ]. The fact that the acute group has no difference from its time-matched control group (0h-PMI) further corroborate the use of Ppia as a reference gene for epilepsy, and shows that controls with a longer postmortem interval (6h-PMI) could create false results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Curiously, although Ppia levels are close between 0h- and 6h-PMI ( Fig 2D ), the decreased Ppia transcript levels in acute group were significant only when compared to 6h-PMI ( Fig 3D ). Previous studies in epilepsy models indicated Ppia as a potential reference gene [ 16 , 49 ]. The fact that the acute group has no difference from its time-matched control group (0h-PMI) further corroborate the use of Ppia as a reference gene for epilepsy, and shows that controls with a longer postmortem interval (6h-PMI) could create false results.…”
Section: Discussionmentioning
confidence: 99%
“…All animal experiments were performed under a protocol approved by the Research Ethics Committee of the Federal University of Alagoas (Permit number: 27/2015) and were consistent with the International guidelines for the ethical use of animals, such as those from the Society for Neuroscience. The research staff monitored the rats’ health throughout the experimental period as described previously [ 16 ]. No animals presented clinical/behavioral signals of pain or unexpected distress used as humane endpoint criteria for euthanasia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rats were kept at 22°C in groups of four per cage with free access to food and water, in a 12-h light/dark cycle (lights on at 08:00 am). Animal health was monitored throughout the experimental period as described previously [ 59 ]. No animals presented clinical/behavioral signals of pain or unexpected distress used as humane endpoint criteria for euthanasia.…”
Section: Methodsmentioning
confidence: 99%
“…It is also unknown how does circadian gene expression relate to induction of spontaneous seizures and epilepsy. In our previous study, we analyzed the temporal profiling of clock genes mRNA levels in the hippocampus of naïve rats ( 61 ). Here, we address this issue by studying these genes in a post-SE model of mTLE, a prototype showing similar epileptogenic and histopathological processes as human mTLE ( 62 ).…”
Section: Introductionmentioning
confidence: 99%